MANAGEMENT OF CLUSTER HEADACHE WITH AYURVEDIC THERAPEUTICS AND MEDICINE: A CASE REPORT - Shivaranjani J Kantharia; S N Gupta; K.B.Patel (International Journal of Applied Ayurved Research, 2016)
Cluster Headache is a neurological disorder characterized by recurrent, severe headache on the one side of the head, typically around the eye. It often recurs at the same time each day during the cluster period, which can last for weeks to months. According to Ayurvedic point of view the main symptom of this disease “Shoola” (pain) occurs because of the vitiation of the Vata dosha. This may be considered as Vatika Shiroroga. A 30 yrs old female patient with a prior diagnosis of Cluster headache was admitted in P.D.Patel Ayurvedic Hospital, Nadiad. She was treated with Ayurvedic treatment including Abhyantara Snehapana with Panchatikta Ghrita, Sarvanga Abhyanga and Bashpa Svedana, MruduVirechana, Niruha Basti, Brumhana Nasya with Brahmi Ghruta and Oral medicament including Shirahshooladi vajra rasa and Pathyadi kvatha. Encouraging result was observed with absolute relief from headache and other associated symptoms of the disease. This case report is presented here to share the encouraging results of Ayurvedic treatment in this particular patient of cluster headache.